HEALTH LEVEL OF BANK USING RISK BASED BANK RATING - Titin RULIANA; Rina Masyitoh HARIYADI; Siti WINARSIH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Level of Health and financial performance of banks is the ability of a bank to conduct banking operations as normal and is able to meet all its obligations properly in a manner that complies with applicable banking. Increasing the effectiveness of health assessment of banks to cope with changes in the banking environment, the banks need improvement with risk approach. This research aims to examine and analyze the Assessment of the level of health of Commercial Banks, based on Bank Indonesia Regulation No. 13 / I / PBI / 2011. This study uses 32 banking companies listed in Indonesia Stock Exchange year period 2012-2014. The analytical tool used this study is the Assessment of the level of health of Commercial Banks against the risk factor using the ratio of net performing loans (NPLs) and Loan to Deposit Ratio (LDR), a factor of corporate governance by using the report self-assessment of good corporate governance, the earnings factor using the ratio of return on assets (ROA) and net interest margin (NIM) and the factor of capital using the ratio of capital adequacy ratio (CAR). Based on the findings, it was concluded as follows: the Assessment of the level of health of Commercial Banks that are in the category of healthy and good assessment in 2012 until 2014. Banks that were rated best based on the health of banks use the following indicators: (1) Net performing loans obtained by PT. Nationalnobu Bank Tbk; (2) Loan To Deposit Ratio by PT. Nationalnobu Bank Tbk .; (3) Return on Assets: by PT. Bank Mestika Darma Tbk, and PT. Bank Rakyat Indonesia Tbk; (4) Net Interest Margin: by PT. Bank Danamon Tbk, and PT. National Savings Bank Tbk .; (5) Capital Adequacy Ratio: by PT. Nationalnobu Bank Tbk.